THE EFFECT OF L- ARGININE ON OXIDATIVE STRESS AND MICROALBUMINURIA IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND CHRONIC KIDNEY DISEASE - L. P. Martynyuk; L. Z. Vons; O. O. Ruzhytska (International Journal of Medicine and Medical Research, 2017)
Background. One of the severest complications of diabetes is diabetic kidney disease (DKD). Microalbuminuria (MAU) is one of the first signals of DKD and an important pathogenetic mechanism of disease progression. With diabetes dramatically antioxidant properties worsen.